Anatomical Survey Versus Fetal Echocardiograms for Diagnosis of Cardiac Defects with a Single Umbilical Artery Cases: A Retrospective Cohort Study and Diagnostic Meta‐analysis. (4th September 2020) - Tonismae, Tiffany; Kline, Jessica H.; Choe, Jennifer J.; Schubert, Frank; Tuuli, Methodius; Shanks, Anthony
Abstract : Objective: To determine the utility of fetal echocardiography in diagnosing cardiac defects in fetuses with a single umbilical artery (SUA). Methods: A retrospective cohort study of prenatally diagnosed SUA was conducted over a 10‐year period at a single institution. Cardiac anatomy on detailed anatomical survey was compared with fetal echocardiogram for fetuses with prenatally diagnosed SUA. A diagnostic meta‐analysis of studies comparing fetal anatomical survey to fetal echocardiogram in fetuses with SUA between 2010 to 2019 was also performed. Results: Three hundred and twenty fetuses with SUA were identified, 113 of which had completed both ultrasound and echocardiography. There were 36 cases of cardiac defects on prenatal echocardiogram and all had abnormal anatomical ultrasounds. There were zero cases of abnormal cardiac exams (0%) when the cardiac views on anatomical survey were normal. The sensitivity, specificity, positive predictive value and negative predictive value of ultrasound were 100%, 77%, 73% and 100%, respectively. A summary ROC curve demonstrated a high predictive value of routine anatomic survey for cardiac defects (AUC: 0.99). Conclusion: Anatomic survey is highly predictive in the detection of cardiac defects in fetuses with SUA. Fetal echocardiogram is unnecessary in SUA when cardiac views are normal on ultrasound.